2012
DOI: 10.3945/ajcn.111.020156
|View full text |Cite
|
Sign up to set email alerts
|

Choline intake in a large cohort of patients with nonalcoholic fatty liver disease

Abstract: Decreased choline intake is significantly associated with increased fibrosis in postmenopausal women with NAFLD. The Pioglitazone vs Vitamin E vs Placebo for Treatment of Non-Diabetic Patients With Nonalcoholic Steatohepatitis trial was registered at clinicaltrials.gov as NCT00063622, and the Treatment of Nonalcoholic Fatty Liver Disease in Children trial was registered at clinicaltrials.gov as NCT00063635.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
81
0
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(87 citation statements)
references
References 63 publications
2
81
0
4
Order By: Relevance
“…Experiments in rodents have revealed molecular underpinnings of liver fat accumulation using methionine and choline deficient (MCD) diets [30,41], and diminished choline intake has also been associated with a more aggressive NAFLD course in humans [42]. The ability of experimental MCD diets to trigger steatosis and liver injury is facilitated by abundant mono- or disaccharides in the diet, because replacing these simple carbohydrates with starch markedly ameliorates the adverse histopathological effects of the MCD diet, a portion of which is hypothesized to occur through increased de novo lipogenesis [31,43].…”
Section: Discussionmentioning
confidence: 99%
“…Experiments in rodents have revealed molecular underpinnings of liver fat accumulation using methionine and choline deficient (MCD) diets [30,41], and diminished choline intake has also been associated with a more aggressive NAFLD course in humans [42]. The ability of experimental MCD diets to trigger steatosis and liver injury is facilitated by abundant mono- or disaccharides in the diet, because replacing these simple carbohydrates with starch markedly ameliorates the adverse histopathological effects of the MCD diet, a portion of which is hypothesized to occur through increased de novo lipogenesis [31,43].…”
Section: Discussionmentioning
confidence: 99%
“…Studies simulating methyl-deficient diets have reported disorders in protein synthesis in the liver and fatty liver as well as muscle disturbances [24,25,26]. Betaine [27,28,29,30], choline, or folate [31] were able to reverse alcohol-related or non-alcohol related liver disturbances, probably via epigenetic regulation [32] or lipid-related mechanisms.…”
Section: Metabolic Burden Of a Methyl-deficient Dietmentioning
confidence: 99%
“…This is supported by data in humans showing that dietary choline deprivation leads to the development of fatty liver differentially depending on sex and genetic variations in 1‐carbon genes (68). A recent publication showed that, in biopsy‐characterized postmenopausal women, low choline intake was associated with worse fibrosis (27), highlighting choline as an important nutrient in NAFLD progression. Our study provides novel insights into the contributions of choline‐related SNPs to steatosis severity.…”
Section: Discussionmentioning
confidence: 99%